V.P. Danilov: Scientific opponent of the “Great Break” - Krasilnikov Sergey (Крестьяноведение, 2025)
The past century left a deep mark not only on the life and fate of the Russian peasantry as a civilizational social-cultural community but also on the work of historians who studied it. Among them, one of the most outstanding is Viktor Petrovich Danilov. As a historian of the Soviet era, he enjoyed well-deserved respect and reputation on both sides of the border, having developed a platform for their creative union in two successive documentary works on the tragic history of the Soviet peasantry in the era of etatization of the agrarian economy. The article aims at assessing the professional and personal experience of a participant of the famous Danilov’s projects, a representative of the next generation of historians who grew professionally while working with Danilov. The author considers some principles of collective work on serial documentary publications, difficulties of such work and ways to overcome them, which allowed to achieve the final results, focusing on the development of alternativeness in the transformations of the 1920s. Due to its consistent rejection of Stalin’s solution to the peasant question, Danilov’s legacy serves as a moral challenge to conformism as a widespread historical corporate disease.